Mengapa Konservasi Arkeologi? - Sulistiono, Budi (Buletin Al-Turas, 2006)
A great nastion are people which appreciate the culture values that are inherrited to them. The treasures of the culture result have to be saved, kept, and preserved to avoid its extintion. Therefore, it is very important to make conversation for the archaeological treasures